2010
DOI: 10.1128/jvi.02486-09
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses and Permissiveness to Ranavirus Infection of Peritoneal Leukocytes in the FrogXenopus laevis

Abstract: Ranaviruses such as frog virus 3 ([FV3]family Iridoviridae) are increasingly prevalent pathogens that infect reptiles, amphibians, and fish worldwide. Whereas studies in the frog Xenopus laevis have revealed the critical involvement of CD8 T-cell and antibody responses in host resistance to FV3, little is known about the role played by innate immunity to infection with this virus. We have investigated the occurrence, composition, activation status, and permissiveness to infection of peritoneal leukocytes (PLs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 47 publications
6
135
1
2
Order By: Relevance
“…In Xenopus laevis, the liver often becomes infected after other organs (Robert et al 2005). It also is possible that qPCR detected quiescent ranavirus in circulating macrophages (Morales et al 2010 The trend of decreasing ranavirus prevalence over time suggests that bullfrog tadpoles have the capability of clearing this pathogen, which is the first direct evidence for this species. Clearing of ranavirus infections has been reported in Xenopus laevis (Gantress et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Xenopus laevis, the liver often becomes infected after other organs (Robert et al 2005). It also is possible that qPCR detected quiescent ranavirus in circulating macrophages (Morales et al 2010 The trend of decreasing ranavirus prevalence over time suggests that bullfrog tadpoles have the capability of clearing this pathogen, which is the first direct evidence for this species. Clearing of ranavirus infections has been reported in Xenopus laevis (Gantress et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as target organs may differ for different types of virus and host species, our results may be limited to American bullfrog tadpoles and the isolates used in our study. Also, a positive qPCR result indicated that ranavirus DNA was present (Green et al 2010); however, distinction be tween active and quiescent infections (Morales et al 2010) could not be made. Other techniques, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Robert et al ( 2007 ) demonstrated that X. laevis , which is generally resistant to FV3 infections, can be asymptomatic carriers. In a subsequent study, Morales et al ( 2010 ) showed that peritoneal macrophages sometimes harbor quiescent FV3 infections for at least 3 weeks. Asymptomatic infections can be reactivated in animals that are immunocompromised by γ-irradiation (Robert et al 2007 ).…”
Section: Persistence Of Ranaviruses In the Environment And Carriersmentioning
confidence: 93%
“…TNF-α and IL-1β are common proinflammatory cytokines released from cells prior to the in flammation. Increased ex pression of TNF-α and IL-1β were reported in FV3-infected Xenopus and EPC cells and EHNV-infected EPC cells (Morales et al 2010, Holopainen et al 2012). In our study, GSIV infection triggered rapid and high expression of MIF, TNF-α and IL-1β in the spleen at 3 dpi, which may subsequently influence viral replication.…”
Section: Discussionmentioning
confidence: 94%
“…Recent ly, the Chinese giant salamander MIF gene sequence was identified, and its encoded protein was shown to have enzymatic redox and tautomerase activity, and was also capable of inhibiting the migration of macrophages (Wang et al 2013). Rana virus infection can up-regulate pro-inflammatory cytokines such as TNF-α and interleukin-1β (IL-1β) in fish and frogs (Morales et al 2010, Holopainen et al 2012, but the inflammatory responses to rana virus infection have not been characterized in amphi bian hosts, such as the Chinese giant salamander.…”
Section: Introductionmentioning
confidence: 99%